Diversity Oriented Synthesis of Oxygen-Heterocycles, Warfarin Analogs Utilizing Microwave-Assisted Dimethyl Urea-Based Deep Eutectic Solvents. (9th August 2022) - Teja, Chitrala; Garg, Ashna; Rohith, G.K.; Roshini, Hanumanthu; Jena, Sushovan; Nawaz Khan, Fazlur Rahman
Abstract: Deep eutectic solvent (DES) catalyzed, Microwave-assisted one-pot conjugate Michael addition followed by annulation of nucleophiles, 4-hydroxy coumarin, 1, 3-diketone with α, β-unsaturated carbonyl compounds (chalcones) toward benzopyran, pyranocoumarin, xanthene, dihydrofuran, 4-hydroxy-coumarin (warfarin analogs) derivatives has been achieved. It is a one-pot, solvent, metal-free, and green chemical approach with a clean reaction pathway, in high regio, stereo selectivities, and yields under milder MW-irradiation. The easily recoverable DES catalyst and eco-friendly reaction strategy are notable advantages of the current procedure.